The Effect of Inquiry-Based Independent Worksheet Using ICT Towards Science Learning to Embody the Student's Creativity and Characters - Ratna Dewi, Novi; Akhlis, Isa; Nur Aini, Fitria; Taufiq, Muhamad (International Journal of Engineering and Technology, 2018)
This research aimed to find the effect of inquiry-based independent worksheet toward the junior high school students' creativity, characters and concept understanding. Quasi-Experimental with a nonequivalent control group design was applied for this research. Creativity and characters data were obtained by using observation method while the concept knowledge was achieved by using test method. The result showed that the concept knowledge, creativity and character level of experiment class were higher than control class, which had confirmed through the t-test. The result of moment product correlation analysis showed that ICT gave the effect of 39.08% towards creativity level, 49.66% towards character level and 28.26% towards concept understanding in experiment class. The result showed that inquiry-based independent worksheet in science learning gave the influence towards concept understanding, creativity and character level of junior high school students. There are no reports on the advantages of an independent assignment sheet, inquiry-based learning and the use of ICT which come from different and separate researchers. Researchers had previously researched the application of science learning software development with inquiry-based cultural deviance solution to develop the character and creativity of learners.Â